Spontaneous Pneumothorax and Pneumomediastinum Following COVID-19 - Ensieh Vahedi; Seyed Jalal Madani; Hamideh Molaee; Esmat Davoudi-Monfared (Baqiyatallah University of Medical Sciences, 2020)
Background: Pneumomediastinum and pneumothorax are usually rare conditions after pneumonia. This study examines the progress of pneumonia of the coronavirus disease 2019 (COVID-19) to spontaneous pneumothorax and pneumomediastinum in a patient. Case Presentation: The patient was a 40-year-old man who complained of nonproductive cough and dyspnea. He also complained of fever, sore throat, back, and chest pain. The patient used to smoke but now he quit .His O2 saturation was 89% at the time of admission. He was assessed with suspicion of COVID-19. CT scans of the chest showed brief changes of emphysema and a ground glass view was also seen in the lungs. In the patient's tests, RT-PCR testing of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was performed and it was positive. Treatment was initiated and because of the progression of symptoms, the serial CT scanning of the patient's lungs was performed daily; and cavitary changes, air-fluid appearance, and destructive changes of lungs were reported. After eight days, the patient's cough worsened. CT scans of the patient's lungs showed some bullaes, pneumothorax, and pneumomediastinum, thus a chest tube was inserted and oxygen therapy was begun on the patient with 3-6 L/min. After 5 days in CT, the patient was relieved of pneumothorax and pneumomediastinum and after a week, the chest tube came out. Conclusion: Pulmonary lesions of COVID 19 can progress to bullae, pneumomediastinum, and pneumothorax. Deterioration of dyspnea and respiratory symptoms can be a warning of pneumomediastinum and pneumothorax that can be confirmed by graphics and timely treatment of the patient can be life-saving.